Hand Hygiene Compliance among Healthcare Workers in Public-Sector Rural Hospitals in Benin - DEGBEY, Cyriaque; GLELE AHANHANZO, YOLAINE (My University, 2019)
Background: To identify the factors associated with hand hygiene compliance among healthcare workers. Abstract Methods: It was a cross-sectional, descriptive and analytical study conducted in the nine (09) pavilions of Aplahoue District Hospital (Benin). The choice was exhaustive because of the small number of employees. The techniques used for data collection consisted of a survey questionnaire and direct observation when providing health care or services. Comparisons of proportions were made using the chi-square test. To search for associated factors, a univariate analysis of the data by simple linear regression was performed using Fisher’s statistical test with a p value considered significant at a 5% threshold. Results: The overall compliance rate for hand hygiene was 12.15%. Factors associated with compliance rate of hand hygiene were knowledge of hospital-acquired infections from basic training (coefficient = 8.86 and p-value = 0.000), knowledge of hand hygiene in hospital setting from basic training (coefficient = 8.25 and p-value = 0.001), soap allergies (coefficient = -5.46 and p-value = 0.041), wearing short-sleeved scrubs (coefficient = 9.82 and p-value = 0.011) and the professional category (p-value <0.05). Among healthcare professionals, 76.27% have a moderate level of knowledge about hand hygiene; 62.71% know the main mode of cross-transmission of germs between patients in a care facility and 93.22% know all the components of hand hygiene. Keywords: Risk Factors; Compliance; Hand Hygiene; Benin Conclusion: This study allowed us to identify the factors that need to be tackled in order to raise the overall compliance rate for hand hygiene, which is low in the Aplahoue’s hospital